2021
DOI: 10.3390/economies9030096
|View full text |Cite
|
Sign up to set email alerts
|

Work from Home: Measuring Satisfaction between Work–Life Balance and Work Stress during the COVID-19 Pandemic in Indonesia

Abstract: Coronavirus (COVID-19), which hit in early 2020, changed the way people live and work, and affected industries and organizations all over the world. Many organizations have begun to deliver a new way of working to adapt to these shifts effectively using teleworking or a work from home policy. The purpose of this study was to fill the gaps by investigating several potential predictors of job satisfaction during working from home from the impact of COVID-19 such as work–life balance and work stress. Using a quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
195
3
30

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(250 citation statements)
references
References 54 publications
22
195
3
30
Order By: Relevance
“…Different assessments have been reported about the impact of remote work on job satisfaction. For example, some researchers have argued that a linear relationship between job satisfaction and remote work exists since people who work remotely more are more satisfied with their jobs (Irawanto, Novianti & Roz, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Different assessments have been reported about the impact of remote work on job satisfaction. For example, some researchers have argued that a linear relationship between job satisfaction and remote work exists since people who work remotely more are more satisfied with their jobs (Irawanto, Novianti & Roz, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to studies by Schall (2019) and Nuwer (2016), as the intensity of remote work increases, so does job satisfaction, but only to a certain point. Based on recent studies (Irawanto, Novianti & Roz, 2021), the higher the intensity of remote work, the more satisfied employees are. In the group of people who spend only ¼ of their time working remotely, 82% of the respondents said they want to work remotely more often (Buffer and AngelList, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Detrimental effects of working from home is further supported by an Indonesian study. Because employees are still accustomed to having fixed working hours, they are unable to divide their time between work and home life (Irawanto, Novianti & Roz, 2021).…”
Section: Challenges Of Wfhmentioning
confidence: 99%
“…The coronavirus has changed the way people live and work. The study by Irawanto et al [21] revealed that working from home, work-life balance, and work-related stress have significant effects, both direct and indirect, on job satisfaction. In fact, COVID-19 has changed working conditions due to social distancing policies.…”
Section: Introductionmentioning
confidence: 99%